String music of the baroque era for string quatet or string orchestra Violin II - CLARKE, Irma (The Boston Music, 1911)
Manuetto..CorellinGavotte....RameaunLa rejouissance......HandelnBadinerie...J.S. BachnHornpipe and air.......Purcell